2012
DOI: 10.1186/1824-7288-38-33
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic and enzymatic correlations with outcome in neonates with hypoxic-ischemic encephalopathy

Abstract: BackgroundPerinatal asphyxia leading to hypoxic-ischemic encephalopathy (HIE) is a common problem causing multi organ dysfunction including myocardial involvement which can affect the outcome.ObjectiveTo evaluate the myocardial dysfunction in neonates having HIE by electrocardiographic(ECG) and cardiac enzymes (CK Total, CK-MB and Troponin I) and find out the relationship with HIE and outcome.Design/MethodsThis was a hospital based prospective study. Sixty term neonates who had suffered perinatal asphyxia and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 13 publications
7
22
0
Order By: Relevance
“…11 There was a linear relation between the severity of asphyxia as assessed by HIE grading and the CK-MB values. The Percentage of babies with grade three HIE was similar to Rajkumar PS et al, Karnik E et al whereas HIE grade 3 was higher in Jyoti et al 10,12,13 In present study, there was no significant difference in CK-MB values between HIE 1 and 2, whereas between HIE 1 and 3 the rise was statistically significant showing that evaluation of enzymes can be a good tool to assess the severity of HIE. In a study conducted by Merchant S et al also there was a significant difference between HIE1 and 3 ( Table 8).…”
Section: Asphyxia and Hiesupporting
confidence: 45%
See 2 more Smart Citations
“…11 There was a linear relation between the severity of asphyxia as assessed by HIE grading and the CK-MB values. The Percentage of babies with grade three HIE was similar to Rajkumar PS et al, Karnik E et al whereas HIE grade 3 was higher in Jyoti et al 10,12,13 In present study, there was no significant difference in CK-MB values between HIE 1 and 2, whereas between HIE 1 and 3 the rise was statistically significant showing that evaluation of enzymes can be a good tool to assess the severity of HIE. In a study conducted by Merchant S et al also there was a significant difference between HIE1 and 3 ( Table 8).…”
Section: Asphyxia and Hiesupporting
confidence: 45%
“…10,12,13 This may be due to great variation in Twave changes in normal babies in the first week of life. The ECG changes observed in asphyxiated babies is similar to those observed in Rajkumar PS et al, except that in their study, Grade 2 changes were more.…”
Section: Ecg Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…The infl uence of hypoxemia is related to myocardial dysfunction in asphyxiated neonates and is thought to be secondary to direct effect of ischemia of cardiac myocytes (20). Thus, changes in ECG may be seen as a result of myocardial hypoxia in asphyxiated newborns.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Agrawal et al 8 and D H Karunatilaka 9 had shown that creatine kinase increases in asphyxiated group and that the level of rise is proportionate to the stage of HIE. In our study the CK value also varied with different stages of HIE.…”
Section: Comparative Study Of Baseline Characteristics Of Cases and Cmentioning
confidence: 99%